PARENTAL DEATH IN THE LIVES OF PEOPLE WITH SERIOUS MENTAL ILLNESS - Jones, Danson (2003)
Nearly a fourth (22%) of the participants within a research sample of 148 individuals with serious mental illness reported the death of a loved one as a significant loss, and two thirds of these deaths involved the loss of one or both parents. The key determinant of the severity and duration of grief in response to the death of a parent was whether or not there were extenuating circumstances that complicated the death event, such as co-residence with the deceased at the time of death or a lack of regular social contact with anyone other than the deceased. In all instances of severe or prolonged grief, there was no preparation for the parental death, either through preparatory counseling or practical plans for funeral arrangements, financial repercussions, life-style changes, or residential relocation. Mental health agencies serving people with serious mental illness should begin to incorporate financial and emotional preparation for parental deaths and bereavement counseling as essential services.